DINAMIKA GREEN INNOVATION DAN ENVIRONMENTAL PERFORMANCE: PENDEKATAN RESOURCE-BASED VIEW DAN LEGITIMACY THEORY - Putri, Anggi Ariska; Meilani, Sayekti Endah Retno Meilani (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
Perkembangan isu keberlanjutan mendorong perusahaan mengintegrasikan green innovation sebagai strategi unggulan untuk meningkatkan environmental performance. Studi ini mengkaji dampak green process innovation, green product innovation, green image, serta interaksi antara green product innovation dan green image terhadap environmental performance. Berlandaskan teori RBV (Resource-Based View), green innovation dipandang sebagai kapabilitas strategis yang memperkuat daya saing berkelanjutan, sementara Legitimacy Theory menjelaskan bagaimana green image berperan dalam memperoleh dukungan serta kepercayaan pemangku kepentingan dan masyarakat. Studi ini menggunakan analisis regresi data panel melalui metode Panel EGLS (Cross-section random effects) pada 51 perusahaan sektor energi selama periode 2022-2024. Hasil studi menunjukkan green process innovation dan green image berdampak positif terhadap environmental performance. Sebaliknya, green product innovation tidak menunjukkan dampak yang signifikan sehingga belum memberikan kontribusi terhadap performa lingkungan. Temuan menarik muncul pada interaksi green product innovation dan green image berdampak negatif terhadap environmental performance. Studi ini berkontribusi teoretis terhadap literatur green innovation dan implikasi praktis bagi strategi keberlanjutan perusahaan. The development of sustainability issues has encouraged companies to integrate green innovation as a leading strategy to improve environmental performance. This study examines the impact of green process innovation, green product innovation, green image, and the interaction between green product innovation and green image on environmental performance. Based on the Resource-Based View (RBV) theory, green innovation is seen as a strategic capability that strengthens sustainable competitiveness, while Legitimacy Theory explains how green image plays a role in gaining the support and trust of stakeholders and the community. This study uses panel data regression analysis through the Panel EGLS (Cross-section random effects) method on 51 companies in the energy sector during the 2022-2024 period. The results show that green process innovation and green image have a positive impact on environmental performance. Conversely, green product innovation does not show a significant impact and therefore does not contribute to environmental performance. An interesting finding emerges from the interaction between green product innovation and green image, which has a negative impact on environmental performance. This study contributes theoretically to the literature on green innovation and has practical implications for corporate sustainability strategies.